Real-world study of children and young adults with myeloproliferative neoplasms: identifying risks and unmet needs - Sobas, Marta; Kiladjian, Jean-Jacques; Beauverd, Yan; Curto-Garcia, Natalia; Sadjadian, Parvis; Shih, Lee Yung; Devos, Timothy; Krochmalczyk, Dorota; Galli, Serena; Bieniaszewska, Maria; Seferynska, Ilona; McMullin, Mary Frances; et al. (Blood advances, 2022)
Myeloproliferative neoplasms (MPNs) are uncommon in children/young adults. Here, we present data on unselected patients diagnosed before 25 years of age included from 38 centers in 15 countries. Sequential patients were included. We identified 444 patients, with median follow-up 9.7 years (0-47.8). Forty-nine (11.1%) had a history of thrombosis at diagnosis, 49 new thrombotic events were recorded (1.16% patient per year [pt/y]), perihepatic vein thromboses were most frequent (47.6% venous events), and logistic regression identified JAK2V617F mutation (P = .016) and hyperviscosity symptoms (visual disturbances, dizziness, vertigo, headache) as risk factors (P = .040). New hemorrhagic events occurred in 44 patients (9.9%, 1.04% pt/y). Disease transformation occurred in 48 patients (10.9%, 1.13% pt/y), usually to myelofibrosis (7.5%) with splenomegaly as a novel risk factor for transformation in essential thrombocythemia (ET) (P= .000) in logistical regression. Eight deaths (1.8%) were recorded, 3 after allogeneic stem cell transplantation. Concerning conventional risk scores: International Prognostic Score for Essential Thrombocythemia-Thrombosis and new International Prognostic Score for Essential Thrombocythemia-Thrombosis differentiated ET patients in terms of thrombotic risk. Both scores identified high-risk patients with the same median thrombosis-free survival of 28.5 years. No contemporary scores were able to predict survival for young ET or polycythemia vera patients. Our data represents the largest real-world study of MPN patients age < 25 years at diagnosis. Rates of thrombotic events and transformation were higher than expected compared with the previous literature. Our study provides new and reliable information as a basis for prospective studies, trials, and development of harmonized international guidelines for the specific management of young patients with MPN.
Keywords: Humans; Thrombocythemia, Essential; dítě; Child; Polycythemia Vera; Myeloproliferative Disorders; mladý dospělý; dospělí; lidé; Thrombosis; polycythaemia vera; Primary Myelofibrosis; primární myelofibróza; Adult; esenciální trombocytemie; trombóza; Young Adult; prospektivní studie; myeloproliferativní poruchy; Prospective Studies